Balancing Consumer Rights And Tech Progress: Examining Law No. 8/1999's Impact On Innovation - Ilham Ilham; Erniyanti Erniyanti; M. Soerya Respationo; Darwis Anatami (International Journal of Law, Crime and Justice, 2024)
Maritime law enforcement in Indonesian waters, especially in the Riau Islands, is a complex challenge considering the breadth of the territory and the variety of maritime threats faced. The Maritime Security Agency of the Republic of Indonesia (BAKAMLA RI) has an important role in maintaining security and enforcing the law in Indonesian waters. This study aims to analyze the role and authority of BAKAMLA RI in enforcing maritime law and evaluate the effectiveness of the implementation of its duties in the waters of the Riau Islands. This study uses a normative juridical method with a case approach to collect empirical data. The data was obtained through literature studies, analysis of legal documents, and interviews with BAKAMLA RI personnel and related agencies. The analysis was carried out using John Rawls' theory of justice, Lawrence M. Friedman's theory of legal system, and Sudikno Mertokusumo's theory of legal certainty to understand the obstacles and find solutions to improve the effectiveness of maritime law enforcement. The results of the study show that maritime law enforcement by BAKAMLA RI in the Natuna Riau Islands has not been optimal. The main obstacles faced include limited resources, the complexity of maritime crimes, and ineffective inter- agency coordination. Despite having a strong legal foundation, BAKAMLA RI effectiveness in carrying out its duties still needs to be improved through greater budget support, the procurement of advanced technology, and personnel training and capacity building programs. Based on these findings, it is recommended that BAKAMLA RI strengthen coordination with related agencies through the establishment of a joint command center and information system integration. The government needs to provide adequate budget support and strengthen the regulatory framework to support maritime law enforcement. The public is also expected to increase awareness and active participation in maintaining maritime security. With these steps, it is hoped that the effectiveness of maritime law enforcement by BAKAMLA RI can be improved, so that the security and sovereignty of Indonesian waters, especially in the Riau Islands, can be better maintained